Berdayakan UMKM: Strategi Maju dengan Pemasaran Digital Di Desa Kadugede Kecamatan Kadugede Kabupaten Kuningan - welyhadigunawan, welyhadigunawa; Rina Masruroh; Micki Watulandi (PUBLICA: Jurnal Pengabdian Kepada Masyarakat, 2024)
The community service program with the title "Empowering MSMEs: Forward Strategies with Digital Marketing in Kadugede Village, Kadugede District, Kuningan Regency" aims to empower micro, small, and medium enterprises (MSMEs) in the region through the use of digital technology in marketing strategies. MSMEs in Kadugede Village are faced with the challenge of limited knowledge and skills in accessing a wider market using digital platforms, as well as obstacles in technology adaptation. This program is carried out with a training, mentoring, and consulting approach that focuses on improving digital literacy, the use of social media, marketplaces, and website management to maximize product promotion and sales. Collaboration with various parties such as the local government and the digital community also supports the effectiveness of the program.